Optimizing Raw Material Inventory Control with ABC and Min-Max Methods: Optimasi Pengendalian Persediaan Bahan Baku dengan Metode ABC dan Min-Max - Pradinain, Rizky Fadilla; Ernawati, Dira; Dewi, Sinta (Indonesian Journal of Innovation Studies, 2025)
General background: Inventory control is a critical component in the printing industry, where efficiency and accuracy directly affect production continuity and cost management. Specific background: PT XYZ, a printing and packaging company using an offset-based make-to-order system, faces recurring issues of overstock and inefficiency due to the absence of systematic inventory prioritization and stock regulation. Knowledge gap: Prior studies confirm the utility of ABC Analysis and Min-Max Stock methods, but limited research evaluates their combined application in the context of printing industries with fluctuating demand. Aims: This study aims to optimize raw material inventory control of paper and ink through the integration of ABC Analysis and Min-Max Stock methods. Results: Findings reveal that four types of paper and three types of ink fall under category A, and applying Min-Max Stock significantly reduced order frequency and safety stock, achieving cost savings up to 73% for paper and 30% for ink compared to the company’s conventional method. Novelty: The study demonstrates that combining both methods yields higher efficiency and adaptability than using either approach in isolation. Implications: This integrated approach offers strategic guidance for printing companies to achieve sustainable, structured, and cost-effective inventory management. Highlights: Significant cost savings achieved (up to 73% for paper, 30% for ink). Integration of ABC and Min-Max methods ensures efficient and adaptive control. Provides strategic guidance for sustainable inventory management. Keywords: Inventory Control, ABC Analysis, Min-Max Stock, Raw Materials, Cost Efficiency